Factors influencing workplace accidents in Negeri Sembilan's manufacturing sector / Norasyikin Ishak, Nurfarhana Lim Zulkifli Lim and Siti Nur Aqilahizzati Abu Bakri - Ishak, Norasyikin; Zulkifli Lim, Nurfarhana Lim; Abu Bakri, Siti Nur Aqilahizzati (Faculty of Computer And Mathematical Sciences, 2017)
Workplace accidents in Malaysia showed a continuous rising number of cases by 36.96% from 2,429 cases in 2010 to 3,327 cases in 2015. In the year 2015, there were a total 3,327 cases with 214 cases involving death while the rest included non-permanent disabilities and permanent disabilities. Based on the report from the Department of Occupational Safety and Health (DOSH), it shows that manufacturing is the sector that has the highest number of accidents compared to other sectors. Therefore, in order to reduce the accident rate, this paper aims to find out the factors that contribute towards workplace accidents by using secondary data in which the data are obtained from DOSH Seremban, Negeri Sembilan. About 502 data with 10 variables were analysed by using descriptive analysis and Logistic regression analysis. By using the Logistic regression analysis, there were two classifications of accidents which are fatal and non-fatal. The fatal classifications is denoted as "1" and non-fatal classification denoted as "0" : The result shows that there are some characteristics in workplace accidents in the manufacturing sector: (1) Race tends to be significant with the highest contribution being 'Others' which are meant for foreign nationals; (2) Male workers tend to have a higher accident rate compared to female workers; (3) Foreign workers lead in term of nationality; (4) Machines and tools, working environment and other agencies significantly contribute to workplace accidents Based on the overall results the factors of the workplace accidents are found to be most suitable to predict the non-fatal accidents compared to fatal accidents. However, if the sample sizes are much bigger, there could be more fatal accidents. In conclusion, the percentage of the non-fatal accidents is higher than the fatal accidents in the workplace at Negeri Sembilan's manufacturing sector.